Functional Analysis and Experimental Validation of the Prognostic and Immune Effects of the Oncogenic Protein CDC45 in Breast Cancer - Zhang JN; Li LW; Cao MQ; Liu X; Yi ZL; Liu SS; Liu H (Breast Cancer: Targets and Therapy)
Jia-Ning Zhang,1,2,* Lin-Wei Li,1,2,* Man-Qing Cao,1,2,* Xin Liu,1,2 Zi-Lu Yi,1,2 Sha-Sha Liu,1,2 Hong Liu1,2 1The Second Surgical Department of Breast Cancer, Tianjin Medical University Cancer Institute & Hospital, National Clinical Research Center for Cancer, Key Laboratory of Cancer Prevention and Therapy, Tianjin, People’s Republic of China; 2Tianjin’s Clinical Research Center for Cancer, Key Laboratory of Breast Cancer Prevention and Therapy, Tianjin Medical University, Ministry of Education, Tianjin, People’s Republic of China*These authors contributed equally to this workCorrespondence: Hong Liu, Email liuhong_submit@tjmuch.comPurpose: Cell division cycle protein 45 (CDC45) plays a crucial role in DNA replication. This study investigates its role in breast cancer (BC) and its impact on tumor progression.Methods: We utilized the GEO database to screen differentially expressed genes (DEGs) and conducted enrichment analysis on these genes. We established a Nomogram model based on CDC45 and other clinical indicators. Additionally, we performed protein-protein interaction (PPI) network construction, drug sensitivity analysis, and immune correlation analysis of CDC45. The function of CDC45 was further verified through cell and animal experiments.Results: CDC45 is highly expressed in most tumors, including BC. The expression level of CDC45 was significantly associated with age, sex, race, cancer stage, and molecular subtypes (all p < 0.05). CDC45 was incorporated into a Nomogram model, which showed moderate accuracy in predicting patient prognosis. We also analyzed the co-expression genes of CDC45, including TOPBP1, GINS2, MCM5, GINS1, GINS4, POLE2, MCM2, MCM6, MCM4, and MCM7. Furthermore, CDC45 expression was closely linked to immune infiltration levels, immune checkpoint inhibitors, and the therapeutic response to small molecule drugs. Finally, both in vitro and in vivo experiments confirmed the cancer-promoting effect of CDC45 in BC.Conclusion: The expression level of CDC45 is linked to the prognosis, immune infiltration, and drug sensitivity of BC. In vitro and in vivo experiments have confirmed that CDC45 acts as a cancer-promoting protein in breast cancer.Keywords: breast cancer, CDC45, prognosis, immunity, animal experiment